Image Retrival Pada Obyek Lingga Yoni Di Situs Peninggalan Sejarah Trowulan Mojokerto - Nugroho, Hendro; Liantoni, Febri (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2016)
This study contains about Image Retrieval system image on Lingga Yoni at historical sites Trowulan. In the area Trowulan is a legacy of work Majapahit era where the majority of people it is a Hindu, so many relics found in the form of Linga Yoni which serves as the worship of Lord Shiva. Data retrieval image Yoni Linga Linga Yoni as many as 50 images using a digital camera, and the image size Lingga Yoni 200 x 300 pixels in BMP file format. Stages Image Retrieval system on the study include segmentation stages: (1) Smoothing using the method Pas Low Filter to soften the image of the noise; (2) the extraction step texture by using Region Growing by altering the RGB color image is converted into to facilitate the HSL color groups; (3) Region Region Merging Growing did for the incorporation of color image corresponding to the object Linga Yoni; (4) to get to extraction stage form was originally looking for edge detection using Canny edge; (5) the image is converted into binary form to the morphology using opening and closing. At Stages Image Retrieval 50 Linga Yoni image texture extraction step performed using the 4 corners of each feature value GLCM with Different Inverse Moment IDM to revise the results of Image Retrieval using methods Precision and Recall.